Perancangan dan Evaluasi Sistem Informasi Manajemen Aset Printer dan Toner Berbasis Web untuk Operasional Perusahaan - Sukerman; Desi Ramayanti (Arcitech: Journal of Computer Science and Artificial Intelligence, 2025)
Printer asset and toner management in enterprises is often inefficient due to fragmented, manual procedures, which reduce data accuracy and slow operational decisions. Addressing this gap, this study designs and evaluates a web-based printer asset and toner management information system that integrates asset records, toner stock and request monitoring, and incident logging within a single platform with role-based access control. The system also provides dashboard summaries and reporting features to support near real-time monitoring and asset audits. Development followed an Agile methodology to enable rapid iterations driven by user feedback. Evaluation employed black-box testing and User Acceptance Testing (UAT) to verify functional correctness and workflow fit. Results indicate that the system operates as required and improves traceability and operational efficiency compared with the prior manual approach. The study contributes a replicable design and evaluation framework for integrated printer–toner asset management systems in organizations with similar operational characteristics.